Menaces of Ideal Motherhood – A Brief Study of 21st Century Motherhood in The Lowland & The House of Hidden Mothers - Mahato, Subhranil; Saha, Apurba (Green University Review of Social Sciences, 2022)
Motherhood is not a decision taken out of choice. Many a time, women are compelled to become mothers due to the pressure from families, peers and society. It becomes an entrapment, where they are imposed with certain ideas and goals to fulfil like children and a ‘happy’ marital communication. The loss of one’s own identity and accepting an ‘ideal’ one, which is congenial for the traditional setup, motherhood is thus, questioned. However, motherhood—or parenthood, for that matter—is not a proverbial Band-Aid. Not every woman is carved for motherhood, even though then entire world may tell her otherwise. Being biologically capable of giving birth does not mean every woman would want to go through with it. The twenty-first century fiction are paving a path for an obvious change in the image of mother. Authors have resettled themselves from ideal portrayals of enduring, self-effacing women, and toward conflicted female characters, those are in active search of their identity. In this regard, the paper will study Jhumpa Lahiri’s The Lowland and Meera Syal’s The House of Hidden Mothers, which depict the diversity of women, breaking stereotypes and the rejection of subordination, rather than limiting them to an ideal. Green University Review of Social Sciences Dec 2021; 7(1-2): 65-74